Management Implications of Estimating Abundance of Quail Inhabiting Forest Environs in Mexico - Jack C. Eitniear; John T. Baccus (National Quail Symposium Proceedings, 2017)
Estimating abundance of forest quail in Mexico offers unique challenges to wildlife managers. Unlike quail inhabiting grassland, forest quail are often cryptic, live in inaccessible mountainous areas, and unpredictably respond to playback census techniques. During 1996–1999, we estimated abundance of singing quail (Dactylortyx thoracicus) and bearded wood quail (Dendrortyx barbatus) in northeast Mexico. Singing quail were visually counted at El Cielo Biosphere Reserve, Tamaulipas, along 14 transects varying in length from 1,400 to 5,000 m. Because of the cryptic nature of bearded wood quail, visual counts proved unsuccessful in estimating abundance. Therefore, a tape recording of their chorus call was used to determine presence. Vocalizing wood quail were documented at 10 stations on a single 1,000 m transect near Coatepec, Veracruz. Because of the varied habitat types in the area total population estimates were not estimated. Only the numbers present along our transect are reported. Estimates of abundance of singing quail were obtained due to the homogenous habitat. Density estimates from Ejido Lazaro Cardenas for singing quail were 56 quail/45.4 ha (1 quail/0.8 ha). Density estimates for La Cueva were 30 quail/15.9 ha (1 quail/0.53 ha). The management of these quail species presents a substantial challenge for biologists, because of the difficulty in obtaining population estimates. The number of wood quail estimated by each responding individual to the chorus call and possible seasonal elevation shifts of singing quail should be considered when estimates of abundance are used to set harvest regulations.
Keywords: abundance; bearded wood quail; Dactylortyx thoracicus; Dendrortyx barbatus; estimating numbers; Mexico; playback; singing quail; strip